A Ratio Analysis of China Banks - li, yueyang (2015)
Motivation. This study was motivated by the important role that Chinese banks play in the financial system of China. This role is higher than in many other developed and developing countries, because unlike in many other countries, in China banking system provides much more financing to the economy than its stock market. Also, Chinese banks recently became the top-ranking banking organizations globally in international bank rankings. In year 2007 no Chinese bank was in the list of top-10 banks by their pre-tax profit, but already in 2008 five banks from China stepped into the list and two of these banks led the ranking. Key research question. The key research question of this study is how financial performance, financial position, quality of loan portfolio of Chinese banks changed after the global financial crisis of 2007 - 2009? Another important question is to identify the significant and important determinants of the performance of Chinese banks. Methodology. Methodology of this study is based on the list of nine financial banking ratios that describe financial performance of the banks in a comprehensive manner. Included into the analysis are the ratios that describe profitability, liquidity, efficiency, financial leverage, quality of loan portfolio and its performance, and relative size of loan portfolio. Three types of empirical analysis are used in this study – dynamic analysis of the mean financial ratios, testing of the difference between the mean ratios for the crisis period versus the mean ratios in the after-crisis period; and regression analysis of the determinants of ROA and ROE of Chinese banks in the period during the global financial crisis and in the period after the crisis. Regression methodology uses panel data estimation methodology, as well as cross section estimation. The former is based on the averaged across time financial ratios for each bank and the two time period s are considered – 2007-2009 as the crisis period and 2010-2014 as the post-crisis period. Data. The data for this investigation was obtained from specialized well-recognized international financial database Bankscope that is maintained by Bureau van Dijk. Data was collected for 239 Chinese banks over the period from year 2007 to 2014 inclusively. The key results of the study show that the key changes that occurred to Chinese banks during the crisis were the twofold increase in the ratio of non-performing loans, decrease in the debt to total assets ratio, decrease in the NIM ratio, and also significant contraction in the ratio of net loans to total assets. Also, ROA is positively related to NIM, assets turnover, interest cover, and debt ratio.